(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
A new herb species of Urticaceae, Laportea stolonifera B. L. Bhellum & B. Singh, is described and illustrated from a restricted habitat of subtropical forest of Northwest Himalaya, India. The new taxon is vegetatively similar to Laportea ovalifolia (Schumach. & Thonn.) Chew, an African endemic species and Laportea interrupta (L.) Chew but differs by phenotypic characters such as cordate leaves, unbranched inflorescence, stem hairs types, linear cystoliths with varying shapes, and presence of 2 to 3 stolons arising from basal node of stems. The similarity with the allied species is due to similar habitats occupancy, but isolated geographically from each other. Laportea stolonifera is assessed as Endangered, and the population data, ecological parameters and associated taxa are also presented. A key to the genus Laportea is prepared for India has been presented in the text. Bangladesh J. Plant Taxon. 23(2): 189-194, 2016 (December)